PS-050 Inhaled sodium colistimethate-associated thrombocytopenia. A case report. (24th February 2014) - Umerez, M; Gayan, M; Ercilla, M; Ripa, C; Carmona, P; Barral, JOSU; Lizardi, A; Aguirre, I; Mauleón, MD; Lombera, L
Abstract : Background: Inhaled colistimethate is a drug dispensed in hospital pharmacy services, commonly used in obstructive lung diseases. Purpose: To describe and evaluate the causality of a case of thrombocytopenia after initiating inhaled colistimethate treatment. Materials and methods: Thrombocytopenia was reported by a patient in our outpatient hospital pharmacy service when he came to return Promixin (sodium colistimethate) 1 MIU. The clinical record was retrospectively reviewed to evaluate the possible causality by the Karch-Lasagna algorithm. The adverse event (AE) was notified to the regional pharmacovigilance centre, which consulted national and European agencies about more notifications. Results: A 79 year-old man with diffuse interstitial lung disease (DILD) began inhaled treatment with sodium colistimethate 0.5 MIU/12 h to prevent Pseudomonas sp colonisation. Initial platelet level was normal (130, 000 cell /mcL), but after six months' treatment, he presented haematomas in mouth, eye, back and leg with a platelet count of 6, 000 cell/mcL, so colistimethate was discontinued. A week later, after receiving immunoglobulins and corticoids, his platelet level recovered (98, 000 cell/mcL). After six weeks, the platelet level had normalised (205, 000 cell /mcL) and treatment was restarted at the same dose. Thrombocytopenia reappeared (58, 000 cell/mcL) after 15 days of treatment, therefore the drug was definitely stopped. The AE was classified as probable, as it appeared with treatment initiation, disappeared when drug was withdrawn and reappeared after readministration without any alternative explanation. There were no notifications of this AE in the Spanish Pharmacovigilance System and four had been described in the European Medicines Agency database. Conclusions: Inhaled colistimethate-induced thrombocytopenia is a serious, rare AE we need to look out for as part of the pharmaceutical care in lung disease patients. No conflict of interest.